Employee Stock Option Plan and Firm Performance: A Quantile Regression Approach - Ray, Koustubh Kanti (Asian Journal of Empirical Research, 2016)
The study attempts to investigate the effect of employee stock option plans (ESOPs) on the financial performance of Indian non-finance companies. The study employed the quantile regression (QR) model to examine the effect of ESOP on the financial performance of sample companies. The empirical findings suggest that the effect of equity-based payment is positive at the higher performance levels. This indicates that the firms adopted stock-based compensation schemes in their early stage of growth may cause a declining financial performance in compared to the matured firms. Moreover, the findings indicate that the industry plays a significant role in deciding the equity-based compensation and depict a positive impact of ESOP on firm performance. The employee based compensation is also found to be positively associated with the company performance, while the performance is measured through market measures. The findings may be attributed due to the direct linkage of equity-based option schemes to the market performance measures.